Shiga Toxin-Producing Escherichia coli: Detection, Differentiation, and Implications for Food Safety - William J. Zaragoza; Max Teplitski; Clifton K. Fagerquist (EDIS)
Shiga toxin is a protein found within the genome of a type of virus called a bacteriophage. These bacteriophages can integrate into the genomes of the bacterium E. Coli. Even though most E. coli are benign or even beneficial members of our gut microbial communities, strains carrying Shiga-toxin encoding genes are highly pathogenic in humans and other animals. This 6-page fact sheet discusses the two types of Shiga toxins and the best approaches to identifying and determining which Shiga toxin is present. Written by William J. Zaragoza, Max Teplitski, and Clifton K. Fagerquist, and published by the Department of Soil and Water Sciences, July 2016.